'Amenable to Civil Power': The Influence of the Periphery on British Policy on New Zealand, 1831 to 1837. Issue 3 (4th May 2022) - Moon, Paul
ABSTRACT: From 1831, the New South Wales government employee James Busby began lobbying to be appointed as British representative in New Zealand. Against a backdrop of official British reluctance to intervene in the country, Busby persuaded officials that the indigenous Māori population was not as threatening as was popularly believed in the early nineteenth century, and that its leaders could be persuaded to acquiesce to a more formal British presence in the country. Busby also argued (uniquely among settlers) that Māori chiefs could potentially act in a collective capacity as a form of rudimentary legislature, give the appropriate support. Busby became instrumental in the development of British policy on New Zealand from 1831 to around 1837, and in doing so, demonstrated the extent to which influences from the periphery of the Empire could inform and alter that policy. This article explores some of those core–periphery dynamics, and illustrates aspects of the process by which Britain's stance on New Zealand evolved during this period in response to the reporting and activities of its official appointee to the country.